2019
DOI: 10.1200/jco.2019.37.15_suppl.594
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA (ctDNA) during and after neoadjuvant chemotherapy and prior to surgery is a powerful prognostic factor in triple-negative breast cancer (TNBC).

Abstract: 594 Background: TNBC, the most aggressive form of breast cancer, is treated primarily with chemotherapy, even before surgery (neoadjuvant chemotherapy or NAC). The prognosis and need for adjuvant therapy depends greatly on the tumor response assessed by pathology (pCR). Highly sensitive and specific ctDNA assays have been shown to be of prognostic value in the metastatic settingbut not yet in earlier settings. Methods: Tissue was collected from 26 Q-CROC-03 clinical trial TNBC patients before, during and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Presence of ctDNA within both the single time point and serial sampling could predict relapse across tumour types including within TNBC patients (p = 0.009 and 0.003) [65]. Sample size was small with just 11 and 13 TNBC patients with available samples for single time-point and serial sampling respectively, the results however are supported by other small studies restricted to TNBC patients with similar findings [66,67] suggesting the potential for ctDNA as a biomarker for relapse. What is currently less clear is whether ctDNA detection can be used to direct treatment.…”
Section: Promise Of Liquid Biopsies In Clinical Managementmentioning
confidence: 58%
“…Presence of ctDNA within both the single time point and serial sampling could predict relapse across tumour types including within TNBC patients (p = 0.009 and 0.003) [65]. Sample size was small with just 11 and 13 TNBC patients with available samples for single time-point and serial sampling respectively, the results however are supported by other small studies restricted to TNBC patients with similar findings [66,67] suggesting the potential for ctDNA as a biomarker for relapse. What is currently less clear is whether ctDNA detection can be used to direct treatment.…”
Section: Promise Of Liquid Biopsies In Clinical Managementmentioning
confidence: 58%
“…To date, multiple studies have analyzed the utility of ctDNA to be able to assess disease-free survival (DFS) and overall survival (OS) (Table 3) [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Factors that predict poorer outcomes include concordance between tissue and liquid ctDNA alterations (shown for both TP53 and KRAS mutations) [68,69], higher percent ctDNA (perhaps reflecting higher tumor burden, and higher number of ctDNA alterations [14].…”
Section: Ctdna As a Prognostic Variablementioning
confidence: 99%
“…Multiple studies have shown that ctDNA can be an important prognostic factor. For instance, in triple-negative breast cancer patients who had received or were receiving neoadjuvant chemotherapy, the detection of ctDNA was associated with a significantly worse DFS (p = 0.027) [53]. Additionally, at the last post-chemotherapy pre-surgery time point, detection of ctDNA was strongly associated with shorter DFS (p = 0.013) and OS (p = 0.006) [53].…”
Section: Ctdna As a Prognostic Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, pCR rate was not correlated with ctDNA detection at any time point, while ctDNA positivity after one cycle of chemotherapy was correlated with shorter DFS and OS [ 262 ]. Furthermore, Cavallone et al reported that ctDNA detection after neoadjuvant chemotherapy and before surgery was associated to DFS and OS [ 263 ]. A phase II clinical trial (NCT03145961) is recruiting patients to evaluate whether ctDNA detection can be used to detect residual disease after standard primary treatment in early-stage TNBC.…”
Section: Promising Molecular Biomarkersmentioning
confidence: 99%